ACTUAL PROBLEMS OF MARITIME SAFETY AND MODERN WAYS OF ENSURING THE SHIP SECURITY: Array - Melnyk, O.; Onyshchenko, S.; Lohinov, O.; Okulov, V.; Pulyaev, I. (Municipal economy of cities. Series: «Economy science», 2021)
Maritime security in recent decades has always been a separate issue, one that has been acute for both shipowners and crews of seagoing vessels. It has been marked by periods of relative stability and periods of emerging and growing threats, from the days of the sailing fleet to the era of ironclad steam shipbuilding. Certainly, it is difficult to overestimate the significant role of the scientific community, which has long investigated this problem, revealing its theoretical and practical sides. The professional experience of maritime industry specialists has also sufficiently served to ensure that systematic interest in the issue has provided the basis for the development of strategies and integrated approaches that ensure the safety of vessels and crews at modern levels. Without the latest advances in maritime safety, shipping, as an industry, would not be able to achieve the current level of reliability in ensuring shipboard processes. Every generation of mankind has prioritized maritime safety, contributing to improving its standards and stressing the importance of continuous development of the theoretical framework. At least more than twenty million tons of cargo and more than five hundred thousand passengers move daily by water transport, so the concept of maritime safety extends not only to the safety of life at sea, the safety of vessels and the safety of cargo, but also to the prevention of maritime accidents and pollution. The increasing share of maritime and river transport in international freight and passenger traffic has led to the need for increased maritime safety requirements due to the technical upgrading of maritime transport. This process is based on the principles of current control over the process of vessel operation and prompt acquisition of necessary data and relevant information during the voyage, anticipated route and control over the state of work parameters of technical means of the vessel, but the key aspect of safety is assessment of existing threats and development of ways and methods of ensuring vessel safety.